1959
DOI: 10.1017/s0021859600036777
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation of grassland

Abstract: In many parts of the world crops can only be grown if the land is irrigated. Whilst this is not true of Britain, there are areas, south-east England in particular, where plant growth is limited by lack of water. The effect is particularly noticed on pastures.From the time of its establishment in 1928, Jealott's Hill (mean rainfall 25-7 in.) has been concerned with obtaining the maximum production from grassland. This involved not only trying to increase the over-all yield, but attempting to maintain as constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
1

Year Published

1960
1960
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 7 publications
1
9
1
Order By: Relevance
“…Under dry conditions, irrigation improves the uptake and utilization of N. Usually it fails to improve response to N of mixed swards because it also enhances the contribution from clover in the control plots (4,9,14). It is perhaps not surprising that, where shortage of nitrogen limits production, white clover, which can fix nitrogen, will make a greatly increased contribution when an inadequate moisture supply is corrected.…”
Section: Some Practical Considerationsmentioning
confidence: 99%
“…Under dry conditions, irrigation improves the uptake and utilization of N. Usually it fails to improve response to N of mixed swards because it also enhances the contribution from clover in the control plots (4,9,14). It is perhaps not surprising that, where shortage of nitrogen limits production, white clover, which can fix nitrogen, will make a greatly increased contribution when an inadequate moisture supply is corrected.…”
Section: Some Practical Considerationsmentioning
confidence: 99%
“…Natural rainfall in Britain varies greatly from month to month, from year to year, and from the drier eastern counties of England across to the higher rainfall areas in the west. Herbage yields may be affected by soil-moisture deficits and it has been found that white clover does not grow as well as perennial ryegrass when a moisture deficiency exists (8). A relatively light application of N fertilizer has been found to reduce the clover content of pastures at Hurley, total production not being increased until 235 kg N/ha were applied annually (6).…”
Section: Introductionmentioning
confidence: 99%
“…Overwatering may depress yields (12,15), but this is unlikely on a free-draining soil (16). Apart from any possible loss in yield or waste arising from overwatering, practical considerations, to keep labour and equipment costs to a minimum, would require that swards should be irrigated as infrequently as possible, consistent with a worthwhile improvement in yield.…”
mentioning
confidence: 99%
“…This suggests that economy in both the amounts of water used and in the frequency of irrigation may be achieved by applying water only in sufficient quantities to enable the roots in the upper horizon of soil to absorb the nutrients while making further use of water from a greater depth. The work reported here investigated the efficiency of use of irrigation water, particularly when used in quantities less than that indicated by the soil water deficit INTRODUCTION Previous reports on the irrigation of grass or grass/clover swards have shown that the more frequently a sward is irrigated and the nearer to field capacity the soil is maintained the greater is the yield response to irrigation (12,13,16).…”
mentioning
confidence: 99%